Enhanced performance of TiO2 doped with aluminum for the photocatalytic degradation of a mixture of plasticizers. Issue 1 (February 2022) - Villarreal-Morales, Romeo; Hinojosa-Reyes, Laura; Zanella, Rodolfo; Durán-Álvarez, Juan Carlos; Caballero-Quintero, Adolfo; Guzmán-Mar, Jorge Luis
Abstract: The Al-doped TiO2 catalyst was synthesized by microwave-assisted sol-gel method. The physicochemical properties of the samples were determined by XRD, XPS, SEM, TEM, UV-Vis DRS, Raman spectroscopy, nitrogen physisorption, zetametry, and photoelectrochemical analysis. MP-AES determined the aluminum content in the catalysts. The evaluation of Al-doped TiO2 photocatalytic activity for degradation of a plasticizer mixture (bisphenol A (BPA) and 4-tert butylphenol (4tBP)) was performed under UV and simulated solar light. The catalysts showed anatase crystalline phase, spherical morphology, and the crystallite size decreased as the Al content increased in TiO2 . The substitutional doping of Al 3+ ions incorporated into the TiO2 crystal lattice improved the photocatalytic performance of TiO2 due to the enhanced surface acidity, and surface area, and reduced e - -h + recombination rate. A central composite design (CCD) with surface methodology was applied to identify the optimal degradation conditions evaluating the effect of Al doping within the content range 0.05–0.5 wt% on TiO2 and solution pH in the photocatalytic reaction (3, 6, and 9). The Al-TiO2 0.05% catalyst showed enhanced photocatalytic performance at pH 4.9, allowing 55% and 61% degradation percentages for 4tBP and BPA in 3 h under UV light irradiation. The photocatalytic oxidation mechanism of 4tBP and BPA with scavengers revealed that h + and O2 - were the major reactive species. The transformation products of 4tBP and BPA were identified by LC-MS technique. Coexistent substances in the WWTP showed no inhibitory effects against the photocatalytic decomposition of 4tBP and BPA, and the Al-TiO2 catalyst demonstrated stability during the recycling experiments. Graphical Abstract: ga1 Highlights: Al is effectively incorporated in TiO2 lattice by microwave assisted sol-gel method. Al incorporation in TiO2 enhances specific surface area and acidity and retards charge carrier recombination. Al-TiO2 shows enhanced activity on plasticizers degradation under UV and solar light. BPA and 4t BP degradation reaction pathways using Al-TiO2 photocatalyst under UV irradiation are proposed. Coexistent substances in WWTP do not affect plasticizers photocatalytic degradation.